2021
DOI: 10.3390/cryst11060665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrafine Metakaolin on the Properties of Mortar and Concrete

Abstract: This study investigated the influence of ultrafine metakaolin replacing cement as a cementitious material on the properties of concrete and mortar. Two substitution levels of ultrafine metakaolin (9% and 15% by mass) were chosen. The reference samples were plain cement concrete sample and silica fume concrete sample with the same metakaolin substitution rates and superplasticizer contents. The results indicate that simultaneously adding ultrafine metakaolin and a certain amount of polycarboxylate superplastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Zhang S. et al, 2021 compared the mechanical properties of specimens containing 100 wt% cement, 15 wt% ultra-fine MK and 15 wt% SF instead of cement. It was concluded that there is not much difference in compressive strength between the specimens containing 15 wt% MK and 15 wt% SF [26]. Zidi Z., et al, 2021 assessed the effect of curing conditions on the compressive strength of MK-based geopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang S. et al, 2021 compared the mechanical properties of specimens containing 100 wt% cement, 15 wt% ultra-fine MK and 15 wt% SF instead of cement. It was concluded that there is not much difference in compressive strength between the specimens containing 15 wt% MK and 15 wt% SF [26]. Zidi Z., et al, 2021 assessed the effect of curing conditions on the compressive strength of MK-based geopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common environmental impact abatement techniques in concrete industry is the replacement of cement and natural aggregates with mineral materials reclaimed from industrial waste [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the concrete industry currently faces major challenges in finding cost-effective strategies in reducing the carbon dioxide emissions from manufacturing Portland cement [2]. Using mineral materials reclaimed from industrial waste to replace cement and natural aggregates is one of the most common environmental impact abatement techniques in the concrete industry [3][4][5][6][7][8]. Different alternatives, such as crushed glass, glass powder and metakaolin, are considered to be viable solutions for a greener and more sustainable civil construction industry as these secondary raw materials are readily available [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Metakaolin is obtained via an endothermic reaction of kaolin. The dehydroxylation of kaolin starts at 450 °C and continues at a temperature up to 900 °C; amorphous metakaolin Al 2 Si 2 O 7 is obtained at a temperature above 925 -950 °C; at 1050 °C metakaolin transforms into spinel Si 3 Al 4 O 12 and mullite [7]. In terms of reactivity, metakaolin is one of the most effective pozzolans with reactivity of 954 mg Ca(OH) 2 /g compared to 427 g reactivity of silica microspheres and 875 g of fly ash [17].…”
Section: Introductionmentioning
confidence: 99%